2021
DOI: 10.1155/2021/8863487
|View full text |Cite
|
Sign up to set email alerts
|

Variable Speed Limit Control Method of Freeway Mainline in Intelligent Connected Environment

Abstract: Freeway is an important component of transportation system. Bottleneck areas on freeway reduce driving safety and traffic efficiency. The development of intelligent connected technology provides a new idea for traffic management. In order to alleviate traffic congestion on the freeway bottleneck area, this paper proposes a variable speed limit (VSL) control method in intelligent connected environment. In this paper, the METANET model is improved by combining intelligent connected environment and VSL control th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…A different objective function was determined in [20], whose formulation linked accident risk with the adoption of VSLs. The study by the authors of [21] showed a potential reduction in total network times of 25% in urban areas. In [22] the authors evaluated two different VSL strategies for resolving multiple bottlenecks along the same corridor based on flow or density values.…”
Section: State Of Artmentioning
confidence: 99%
“…A different objective function was determined in [20], whose formulation linked accident risk with the adoption of VSLs. The study by the authors of [21] showed a potential reduction in total network times of 25% in urban areas. In [22] the authors evaluated two different VSL strategies for resolving multiple bottlenecks along the same corridor based on flow or density values.…”
Section: State Of Artmentioning
confidence: 99%
“…As a part of the intelligent transportation system (ITS), variable speed limit (VSL) control has been widely used as one of the traffic control measures to improve traffic efficiency [11][12][13], benefit the environment [14,15], and enhance traffic safety [16,17] in bottleneck areas. By adjusting the speed limit of the main line upstream of the bottlenecks, the number of vehicles entering the motorway bottleneck area during the congestion period is controlled within a certain range to keep the traffic state more uniform and stable.…”
Section: Introductionmentioning
confidence: 99%